Book Review of "The Logic of American Nuclear Strategy. Why Strategic Superiority Matters" by Matthew Kroenig - Arjun Banerjee (International Journal of Nuclear Security, 2020)
Matthew Kroenig is among the best regarded names of the modern generation in the nuclear policy and deterrence fields. He is the author of several books and has had a stellar career in both the policy and academic fields, giving him an indubitable edge in translating from English to English - that is, 'policy-ese' English to 'academish' English, and vice-versa. Kroenig is a scholar-practitioner by training having served in the Pentagon, on Presidential campaigns, and currently holding position as Associate Professor at Georgetown University’s Department of Government.